Financial Performance and Share Price of State-Owned Banks - Entis Sutisna; Kartim Kartim; Septyana Prasetianingrum; Yaya Sonjaya; Muhammad Yamin Noch (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
This study aims to examine the impact of the financial performance of state-owned banks (BUMN) on the Indonesia Stock Exchange (IDX) from 2017 to 2022. The population under investigation comprised all state-owned banks publicly traded on the Indonesia Stock Exchange from 2017 to 2022, amounting to 5 banks. The employed sample approach is purposive sampling. The research utilizes secondary data from annual reports and financial reports of state-owned banking businesses (BUMN) that have undergone an initial public offering and are now listed on the Indonesia Stock Exchange between 2017 and 2022. The data in this study will undergo multiple stages of testing, including descriptive statistical tests and classical assumption tests such as normality, multicollinearity, and heteroscedasticity. Additionally, all hypotheses will be tested using the coefficient of determination test, partial test (t test), and simultaneous test (f test). The findings indicated a strong and statistically significant correlation between the Return on Assets variable and stock prices of state-owned banking institutions listed on the IDX from 2017 to 2022. The Return on Equity variable exhibits a noteworthy and adverse impact on stock prices in state-owned banking institutions listed on the IDX for 2017-2022. The Loan deposit ratio variable shows a statistically insignificant negative impact on stock prices in state-owned banking institutions listed on the IDX from 2017 to 2022.